DIRECT BACTERIA COUNTING IN THE BANDA SEA - Ruyitno, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1989)
Bacteria counting in the Banda sea were carried out in two seasons during Snellius II Expedition. In August 1984, representing the southeast monsoon where upwelling is expected, bacteria counts were higher than in February 1985, representing the northwest monsoon where downwelling is expected. Some biological parameters of the Banda Sea were in support of the bacteria numbers in the expected upwelling region.